Analisis kesalahan siswa dalam menyelesaikan soal invers matriks pada kelas XI SMAN 4 Palu - Almahdali , Muh Ikbal; Pathuddin, Pathuddin; Alfisyahra, Alfisyahra; Lefrida , Rita (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
The aim of the research is to summarize the experiences of grade 11 students at SMA Negeri 4 Palu based on Newman's theory. This type of research is descriptive, using a qualitative approach. The research subjects were two students selected from 35 class XI students. The findings of this research are as follows: (1) Not a single subject experienced errors in reading the lesson material, because at that time every subject was considered able to read the lesson material correctly. (2) Not a single subject made a mistake in understanding, as seen in the interview phase. All research subjects were able to provide understandable and questionable information regarding the subject. (3) Each research subject carries out transformation error correction. This transformation error is characterized by the failure of a subset that reduces the problem of the mathematical model. (4) Process skills errors were made by each research subject. This is explained by the subject's understanding of the steps taken in answering the question, but most of it is caused by the subject's errors occurring in the transformation step and the subject being unable to solve mathematical problems accurately. (5) an error in writing the final answer (encoding error) was made by each research subject; This is differentiated by the fact that there are subjects who do not determine the final results of their learning and there are also subjects who fail to determine the final results due to errors in the previous stage.